Efektivitas Konseling Online pada Kesehatan Mental Remaja - Sosialita, Tiara Diah (Universitas Muhammadiyah Metro, 2023)
The aim of this research is to find the effectiveness of online counseling to improve mental health among adolescents. As a never ending problematic situation that adolescents have limited access to the friendly mental health services. Online counseling as a therapeutic tool offer accessibility, convenient, flexibility, anonymity, and other aspects that can not be obtained by face-to-face counseling. This research was conducted to 200 adolescents aged 15-24 years old in pretest-posttest control group design. Participants were included to meet the criteria of: 1) experiencing mental health problems based on screening test used GHQ-12 (General Health Questionnaire); 2) having quality as an online counseling client (access to media technology, feel comfortable with online communication, able to express thoughts and feelings through writing, and have flexible time). After the data was collected, analysis used independent sample t-test formula showed that online counseling effective to improve mental health among adolescents (effect size = 2,87). The flexibility of time and place was mainly formed the benefit of online counseling regarding the participants. Participants was feeling supported and cared by interaction with other group members.